April evaporation in relation to subsequent monsoon rainfall in India - MASKE, S. J.; SAMUI, R. P. (MAUSAM, 1984)
Monthly mean evaporation charts for the months March to May are examined year by year for the period 1965 to 1975 in relation to the behaviour of the subsequent monsoon rainfall in the country. April charts, in general, show two regions, one primary and other one secondary region of high evaporation belt in the years where the subsequent monsoon rainfall is normal over the country. The primary region of high evaporation extends from Gujarat to Andhra Pradesh through Maharashtra and adjoining Karnataka. It is found for both normal and deficient years. In most of the deficient years, viz., 1965, 1968 and 1972, the pattern changes substantially; the secondary region which extends from Rajasthan to Madhya Pradesh disappears from its normal position. No such change in the evaporation pattern is found in the months of March and May. Though secondary region disappears in April 1970 which was a good monsoon year yet there is no shrinking in total area coverage of high evaporation belt. It appears that secondary region has shifted towards west and forms a bigger region of high evaporation belt, in combination with the primary one. April mean evaporation chart may, therefore, serve as a tool for precdicting the behaviour of the subsequent monsoon rainfall in the country.